Prognostic Significance of Transcatheter Aortic Valve Replacement in Aortic Stenosis: The Play of Pressures - Hussein Harb; Sourya Acharya (Journal of Clinical and Diagnostic Research)
A 45-year-old male with a history of hypertension since eight years on tablet Amlodipine 10 mg once a day presented to Department of Medicine with complaints of exertional breathlessness. He reported experiencing NYHA grade 3 symptoms for the past two months, dizziness for one month, and an episode of syncope five days ago. Upon admission to the medical ward, a transthoracic echocardiogram was conducted, which revealed aortic jet velocity (Vmax) of 4.8 m/s, mean aortic Pressure Gradient (PG) of 45 mmHg, LV mass index (LVMi) 128 gm/m2, and aortic valve area of 0.7 cm2 suggesting severe aortic stenosis. Pressure curves prior to Transcatheter Aortic Valve Replacement (TAVR) procedure were measured via two 6-French “pigtail” catheters from Cordis. Catheters were inserted through the stenotic valve to the left ventricle via a vascular access point assigned for the transcatheter heart valve. A second catheter was inserted to the aortic root through a second vascular access point. Both catheters were then connected and measured by a pressure line and transducer. Following careful calibration of the pressure transducer, Left Ventricular (LV) and ascending aortic pressures were recorded concurrently across multiple heartbeats. Left heart catheterisation demonstrated a higher LV pressure compared to aortic pressure [Table/Fig-1]. The patient subsequently underwent TAVR with fluoroscopic procedural imaging [Table/Fig-2]. Post-procedurally, left heart catheterisation showed alignment of LV and aortic pressures [Table/Fig-3]. On follow up, after 30 days, the patient’s dyspnoea had significantly improved and the 2-D echocardiography revealed a decreasing LVMi to 115 gm/m2.